Approaches to the preliminary processing of terms co-occurrence graph in the method of island text clustering - Юсин, Я. О.; Заболотня, Т. М. (Problems of Informatization and Management, 2017)
Three new approaches to the preliminary processing of terms co-occurrence graph in the method ofisland text clustering are proposed in the article. The algorithms that implement these approaches aredefined. Testing of accuracy and speed of island text clustering using the proposed approaches hasbeen carried out.